Susceptibility of peruvian watergrass and rice cutgrass to glyphosate under soil moisture variations. (August 2017) - Scherner, Ananda; Avila, Luis; Schreiber, Fabio; Kruse, Nelson Diehl; Fernando, Juliana Aparecida; Garcia, Élen Nunes
Abstract: Peruvian watergrass and rice cutgrass are important grass weeds in paddy rice in southern Brazil, mainly due to the low efficacy of non-selective herbicides against these species. The objectives of this study were (1) to evaluate the susceptibility of peruvian watergrass to glyphosate under soil moisture variations, (2) to investigate the effect of soil moisture variations in the control efficiency of glyphosate on peruvian watergrass and rice cutgrass, and (3) to determine the leaf blade and stem anatomical features of both species under flood conditions. Three experiments were conducted, two in a greenhouse and one in laboratory conditions. The first experiment was conducted using three soil water contents (field capacity, saturated and flood conditions) and nine doses of glyphosate to evaluate peruvian watergrass control and dry biomass reduction. The same factors and evaluations were used in the second experiment, however with the addition of the rice cutgrass species. Plants of both species, grown under flood conditions, were collected for histological analysis in the third trial. The susceptibility of these grass weeds was greatly reduced under flood conditions, particularly peruvian watergrass. There were anatomical differences between the two species, but these may not influence the efficacy of the chemical control. Their morphological differences are therefore expected to be involved in their tolerance to glyphosate. Highlights: Flood reduces glyphosate efficacy against Peruvian watergrass and rice cutgrass. Rice cutgrass is more susceptible to glyphosate than Peruvian watergrass. Flood greatly increases Peruvian watergrass biomass production. Species anatomical traits are different but are not linked with glyphosate efficacy. Plants morphological traits are more likely to hamper glyphosate activity.